High performance work practices and project manager turnover in IT projects - Smolander, Satu (My University, 2017)
The focus of this study is to present how high performance work practices (HPWPs) can be used to prevent, manage or sort out the replacement of project manager (RPM) in IT projects. HRM has secured its role as an important factor affecting organizational performance, and thus it can be assumed that it also plays a part in project performance. The project manager has a key role when it comes to project success and so it is vital to analyse what can lead to RPM and what effects it might have on project performance. The idea behind the emphasis of this study is that the two well known fields of strategic HR and project management can be combined to mitigate the negative impacts of the common but less researched phenomenon of RPM. The study is based on qualitative research. A group interview was conducted with HR and project management professionals in a large Finnish IT sector organization to find out whether HPWPs are already used in the context of RPM. With an extensive literature review as the backbone, the interview was used to gather empirical data on the phenomenon. In addition to providing an overview on the theoretical frameworks of HPWPs and IT project management, this study shows how, through the use of HPWPs, RPM could be prevented, managed or sorted out. The gathered data provides real life examples and suggests ways to deal with different scenarios related to RPM.
Keywords: Project manager; turnover; high performance work practices; IT project; fi=Tietotekniikka (KTM)|en=Computer Science|